205k views
3 votes
Marlena solved the equation 2x + 5 = –10 – x. Her steps are shown below.

2x + 5 = –10 – x

3x + 5 = –10
3x = –15
x = –5

2 Answers

4 votes

Answer:

-5

Explanation:

User Deepwinter
by
5.7k points
5 votes

Answer:We are asked to evaluate Marlena's solution in solving the expression below: 2x+5 = -10 -x

The first step is to re-write the expression and transpose same terms in the left side while all numbers are transferred to the right side such as shown below:

Step 0: 2x+5 = -10 -x

Step 1: 2x + x = -10 -5

Step 2: 3x = -15

Step 3: x =-15/3

The answer is x=-5.

Explanation:

User Gian Santillan
by
5.8k points